Violence under the Banner of Religion: The Case of Laskar Jihad and Laskar Kristus - Mulyadi, Sukidi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2003)
In the course of its history, religion has had a dual function in plural societies. Many scholars and religious leaders agree that religion has had a role in fostering peace, harmony and civility. However, other scholars see religion as a source of conflict and violence. The latter view is supported by numerous incidents of religious violence around the world. The work of Juergensmeyer for example, clearly shows how violence has occurred and spread under the banners of all religions.DOI: 10.15408/sdi.v10i2.631